2019
DOI: 10.21873/invivo.11700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Neoadjuvant Chemotherapy With Gemcitabine Plus S-1 for Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Background/Aim: Little is known about the efficacy of neoadjuvant chemotherapy (NAC) with gemcitabine plus S-1 (GS) for patients with resectable pancreatic ductal adenocarcinoma (R-PDAC). The aim of this study was to investigate differences in the long-term outcome of patients with R-PDAC undergoing pancreatectomy with and without NAC-GS to clarify the clinical significance of NAC-GS. Patients and Methods: A total of 77 patients with R-PDAC who were scheduled for pancreatectomy between January 2012 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…The preoperative waiting period has been reported to be 42-124 days. 5,6,19,22,23 In the present study, the median preoperative waiting period was 73 days in the PS group and 79 days in the MS group, which was not different from those of previous reports. The occurrence of severe obstructive jaundice and cholangitis resulted in interruption of NAC(R)T, which consequently led to longer waiting periods.…”
Section: T a B L E 2 Outcome Measurescontrasting
confidence: 73%
“…The preoperative waiting period has been reported to be 42-124 days. 5,6,19,22,23 In the present study, the median preoperative waiting period was 73 days in the PS group and 79 days in the MS group, which was not different from those of previous reports. The occurrence of severe obstructive jaundice and cholangitis resulted in interruption of NAC(R)T, which consequently led to longer waiting periods.…”
Section: T a B L E 2 Outcome Measurescontrasting
confidence: 73%
“…The breakdown of NAC regimen is as follows: gemcitabine in two patients, GS in 62 patients, GnP in two patients, and GnP following GS in one patient. Thus, 92.5% of NAC is the two cycles of GS regimen, the detail of which is described elsewhere [ 17 ]. Cycles of other NAC regimen was flexibly determined in accordance with the patient’s general condition.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 92.5% of NAC were the GS regimen. Suzuki et al, a research group directed by Kubota who is also a member of this research group, reported that radiographic response to the GS therapy was 15.4% of partial response and 84.6% of stable disease in primary resectable PDAC [ 17 ]. All GS group ( n = 38) and 27 of the UFS group ( n = 37) in their prospective randomized control study are also included in this study subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathological outcome was better, no survival benefit was seen in NAT patients; in fact, Barbier et al [30] found long-term survival was slightly better in the surgery-first group. [58] Suzuki et al [26] did not recommend GS NAT, and Kurata et al [27] recommended that NAT may be applied to borderline resectable and locally advanced PDAC to enable surgical resection, but upfront surgery was desirable for primary resectable PDAC. No difference in the mOS was observed in the Palmer et al [23] study either.…”
Section: Survivalmentioning
confidence: 99%